Evaluasi Sistem Informasi Administrasi Siswa Menggunakan Metode PIECES serta Rekomendasi Perbaikannya : Studi Kasus: TK Harapan Sejahtera - Vira Arif Rakhmatunnisa; Elin Rosliani (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2026)
Student data management systems in early childhood education institutions often still rely on conventional paper-based approaches, a situation that potentially hampers the overall effectiveness of administrative services. This study aims to evaluate the student information administration system at TK Harapan Sejahtera, Garut, using the PIECES analytical framework encompassing Performance, Information, Economy, Control, Efficiency, and Service dimensions. A descriptive qualitative approach was employed through participatory observation, semi-structured interviews with four teachers who simultaneously perform administrative functions, and documentation study. The findings reveal several interrelated structural barriers: searching data for 46 active students requires 8–12 minutes per transaction due to reliance on physical archives; monthly attendance recapitulation consumes 1–2 hours of teachers' time outside teaching hours; and routine expenditures for administrative consumables reach Rp150,000–Rp250,000 per month. The absence of dedicated administrative staff forces teachers to bear a dual burden that diminishes the quality of lesson preparation. From a data security perspective, there are no adequate backup mechanisms or access controls, leaving physical archives vulnerable to damage and loss. Based on these findings, this study recommends a phased and realistic digitalization approach, including the use of structured spreadsheets, cloud-based storage, digital communication with parents, and technology training for teaching staff. Implementation of these recommendations is projected to reduce data retrieval time by more than 80% and improve the quality of information services to school stakeholders.